Analysis of Perceived Ease of Use and Perceived Enjoyment on Behavior Intention in Digital Payment on Generation Z in Sukabumi City - Jaya, Umban Adi; Kusnara, Hasti Pramesti; Hodijah, Cucu; Yunita, Melda; Kusumadewi, Ade Nurhayati (Ekonomis: Journal of Economics and Business, 2024)
This research explores the influence of perceived ease of use and perceived enjoyment on behavioral intentions to use digital payments among generation Z in Sukabumi City. With a quantitative approach and explanatory research type, a sample of 100 respondents used a questionnaire as a data collection instrument. Data analysis in this study used multiple linear regression. The research results show that perceived enjoyment has a significant effect on behavior intention, but perceived ease of use does not have a significant effect on behavior intention in generation Z in Sukabumi City